2021
DOI: 10.1002/sd.2276
|View full text |Cite|
|
Sign up to set email alerts
|

Transdisciplinary research in natural resources management: Towards an integrative and transformative use of co‐concepts

Abstract: Transdisciplinary research often utilizes collaborative ways of knowledge production to enable deliberate transformations towards sustainability. Multiple concepts with varying definitions are applied, leading to confusion in the aims and uses of these concepts. In this article, we review five concepts relevant to the current debate on the new collaborative ways of knowledge production in transdisciplinary research. We focus on the concepts of co‐creation, co‐production, co‐design, co‐learning, and adaptive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 159 publications
(334 reference statements)
2
32
0
Order By: Relevance
“…The results of our interviews showed that interviewees shared a common understanding of co‐design in the context of agricultural biodiversity conservation, reflecting the definitions in the current literature (Hakkarainen et al., 2021; Marin et al., 2016; Page et al., 2016). Co‐design was described in the interviews as a process of shared learning that facilitates a continuous eye‐to‐eye exchange between farmers, scientists and other stakeholders over time.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The results of our interviews showed that interviewees shared a common understanding of co‐design in the context of agricultural biodiversity conservation, reflecting the definitions in the current literature (Hakkarainen et al., 2021; Marin et al., 2016; Page et al., 2016). Co‐design was described in the interviews as a process of shared learning that facilitates a continuous eye‐to‐eye exchange between farmers, scientists and other stakeholders over time.…”
Section: Resultssupporting
confidence: 72%
“…Hakkarainen et al. (2021) recently compared the different ‘co‐concepts’ and conceptualized co‐design, following Mauser et al. (2013), as a first step in the process of co‐creating knowledge, ‘where actors articulate their positions, determine the concepts, the skills and the solutions’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has grown into a diverse field, evolving from largely hypothetical contributions on how to coordinate and carry out concerted processes, including interaction of actors from in- and outside of academia, to concrete examinations of particular cases located around the globe (Lang et al 2012 ; Darbellay 2015 ; Polk 2015 ; Zscheischler and Rogga 2015 ; Turnhout et al 2019 ; Bergmann et al 2021 ; Jahn et al 2021 ). Methods have also advanced to focus on the process of knowledge co-production and co-design as well as the testing of sustainability solutions (Pohl and Hirsh-Hadorn 2007 ; 2008 ; Giuseppe 2015 ; Moser 2016 ; Felt et al 2016 ; Renn 2021 ; Hakkarainen et al 2021 ). This has also opened doors to the development of approaches and frameworks for the design, evaluation, and proper financing of more robust collaborative processes (Roux et al 2010 ; Taylor et al 2016 ; Luederitz et al 2017 ; Bernert et al forthcoming; Simon et al 2018 ; Williams and Robinson 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gathering knowledge from a diverse group of stakeholders is pertinent for mapping out these cause-effect chains. Firsthand knowledge from the people that live with and use the lake systems can be significant sources of information (Hakkarainen et al, 2021), with co-creation processes allowing the different actors to appreciate epistemological differences. From outlining the user groups within the system to detailing the history of the system, personal accounts of the residents can "fill in" gaps about how the lake is integrated into the local community and economy (e.g.…”
Section: Existing Knowledge Sources 511 Local Indigenous and Stakehol...mentioning
confidence: 99%